2020
DOI: 10.21037/qims-20-651
|View full text |Cite
|
Sign up to set email alerts
|

Collagen deposition in the liver is strongly and positively associated with T1rho elongation while fat deposition is associated with T1rho shortening: an experimental study of methionine and choline-deficient (MCD) diet rat model

Abstract: Background: A number of questions concerning the histological mechanism of elongated T1rho in liver fibrosis remain unanswered. Using a rat model of non-alcoholic fatty liver disease (NAFLD) induced with methionine and choline-deficient (MCD) diet, the primary aim of this study is to clarify whether collagen deposition per se causes liver T1rho elongation.Methods: There were 45 rats in the NAFLD model group and 8 rats in the control group. NAFLD model rats were fed MCD diet for 1, 2, 4, 6, 8, or 10 weeks, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…Decrease of liver T1rho measure in women with aging T1rho (T1ρ) relaxation time describes spin-lattice relaxation in the rotation frame at the presence of an external radiofrequency pulse in the transverse plane. It has been demonstrated that T1rho elongation is a sensitive biomarker for collagen deposition and thus a sensitive biomarker for liver fibrosis (62)(63)(64). To translate liver T1rho MRI into clinical practice, it is important to know the physiological liver T1rho measure in healthy subjects.…”
Section: Increase Of Liver Iron Content With Agingmentioning
confidence: 99%
“…Decrease of liver T1rho measure in women with aging T1rho (T1ρ) relaxation time describes spin-lattice relaxation in the rotation frame at the presence of an external radiofrequency pulse in the transverse plane. It has been demonstrated that T1rho elongation is a sensitive biomarker for collagen deposition and thus a sensitive biomarker for liver fibrosis (62)(63)(64). To translate liver T1rho MRI into clinical practice, it is important to know the physiological liver T1rho measure in healthy subjects.…”
Section: Increase Of Liver Iron Content With Agingmentioning
confidence: 99%
“…36,37 A previous study used a T1ρ relaxation time to detect inflammation in the same MCD diet rat model. 38 They found a weak correlation of liver inflammation with the liver T1ρ values (r = 0.25) but a strong (r = 0.82) and significant positive correlation between liver collagen content and liver T1ρ. In a study of rabbit NASH models, Xie et al reported T1ρ during the hepatobiliary phase with Gd-EOB-DTPA was associated with the inflammation grade (r = 0.79).…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting that several other quantitative MRI parameters have been shown to be correlated with the inflammation grade as well 36,37 . A previous study used a T1ρ relaxation time to detect inflammation in the same MCD diet rat model 38 . They found a weak correlation of liver inflammation with the liver T1ρ values ( r = 0.25) but a strong ( r = 0.82) and significant positive correlation between liver collagen content and liver T1ρ.…”
Section: Discussionmentioning
confidence: 96%
“…In the clinical setting, T 1ρ relaxation measurements could provide important insights into disease diagnosis and progression 33,40–42 . However, small B 0 and B 1 variations are inevitable and interfere with the T 1ρ quantification.…”
Section: Discussionmentioning
confidence: 99%